Pengujian ISO 25010 Pada Smart Chair Akupresure Berbasis Internet Of Things (IoT) - Diki Daryanto; M. Khairul Anam; Yoyon Efendi; Rahmaddeni Rahmaddeni (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2022)
Smart chair acupressure is a technology that has been built using the application of the internet of things concept. The purpose of this study was to determine the quality level of the Acupressure Smart Chair, so that there are no errors in some features and the occurrence of errors in its functionality, which must be in accordance with the specified usability, the researchers conducted a test by utilizing the characteristics of ISO 25010. Related to the researcher's reasons taking ISO 25010 as one of the tests on the acupressure smart chair is because the smart chair acupressure technology cannot be said to be feasible because there has been no testing carried out in the measurement, the researchers used ISO 25010 which utilizes several characteristics that can be used such as functional suitability, usability and performance efficiency which focuses on measuring the electronic equipment used. Basically the concept used in this research is the internet of things which is a system that functions to control and simplify the workings of acupressure massage techniques for users. Whereas other problems that occur and arise often depend on customer satisfaction related to the quality provided on software and devices. This study uses the ISO 25010 method as the standard for the feasibility test on the device, where ISO 25010 basically also has 8 characteristics. In this study, to test the smart acupressure hair, the researchers used 7 characteristics that exist in ISO 25010, namely functional suitability, compatibility, usability, performance efficiency, reliability, maintability and portability. The instrument used is looking for an approach using the formula for reliability testing and processing on SPSS software. The results obtained from this study are that the acupressure smart chair has not been able to meet the ISO 25010 standard because the results obtained are 34.9% with an alpha cronbch value of 0.46 (unacceptable)